Data Collision Avoidance based on TDMA in LoRa Wireless Sensor Networks - Bhawiyuga, Adhitya (Faculty of Computer Science (FILKOM) Brawijaya University, 2024)
Wireless Sensor Network has an applicative function and a broad discussion area so that it becomes an interesting research topic to discuss. WSN connects communications from several nodes in one network. In order to make each data can be sent, a communication module is needed. LoRa is a communication module that allows each node to make long range communication. However, one of the issues of WSN is that every communication on the node to exchange data uses a time reference from the respective local clock. The difference in time reference in each node will interfere with the process of arranging the communication time scheduling in each node. Time scheduling is necessary to avoid data collision, to apply low power to the system, and to schedule two-way transmissions on LoRa. To manage a scheduling, the time synchronization method is required to apply to equalize the time in each node in a network. The algorithm for time equalization and dividing the time slot for data transmission between nodes on the WSN is the Timing-sync protocol for sensor networks (TPSN) and Time Division Multiple Access (TDMA). This paper will explain the wireless communication method using TDMA based on the LoRa communication module.